The economic implications of trade policy reform in South Africa for the automotive industry in the Eastern Cape Province - Onyango, Donald Otieno (Rhodes University, Faculty of Commerce, Department of Economics, 2000)
South Africa is no longer a pariah state and has been fully integrated into the global family of nations. With the country's accession to multilateral agreements like the World Trade Organization (WTO), there has been pressure on the government to abandon its hitherto protectionist trade regime in favour of free and fair trade. Trade liberalisation has had profound implications for the country's manufacturing sector in general, and the automotive industry in particular, which has seen tariff protection radically slashed and import restrictions greatly eased. Not only has the market share of domestic producers fallen, but increases in exports have to date not matched those of imports. As a result there has been a deterioration in the sector's balance of trade and a reduction in employment levels, at a time when the country desperately needs to create new jobs. Recent developments, however, suggest that this scenario may be set to change. The thesis applies orthodox neoclassical and heterodox approaches to trade policy to an assessment of the likely economic impact of trade liberalisation on the automotive industry in the Eastern Cape, and by extension nationally. The thesis argues that reliance on orthodox trade theory to inform the direction of trade policy, especially in a developing country context, is unlikely to bring about an adequate increase in the level of exports and employment. This is because liberalisation of the import regime is likely to increase import levels without necessarily stimulating export levels, a scenario which serves to negate the presupposed benefits of liberalisation. The study uses information from surveys conducted on both motor vehicle assemblers and component manufacturing firms to investigate the effect of trade liberalisation on the sector in the Province and finds that, by and large, the motor assemblers have not fared as badly as expected and have in fact positioned themselves to export more vehicles and components. The components sector has had to contend with increased competition from cheaper imports. The thesis, while acknowledging that, as far as possible, free trade is an optimal position, nonetheless argues that governments still have an important role to play in the promotion of industrialisation. The scope of government intervention should, however, be limited to selective interventions which are aimed at counteracting market failure and facilitating innovation and the diffusion of technological know-how. The thesis argues that institution of supply side measures, such as the encouragement of research and development (R&D), skills development and industrial training, is necessary for sustained growth in the manufacturing sector to be realised. The thesis also finds that, contrary to expectations, the liberalisation of the automotive sector has not had the desired effects. Despite an increase in the value of automotive exports and an overall trend towards reduced net foreign exchange usage, employment levels are on the decline. The thesis also finds that without major export initiatives by both motor vehicle assemblers and component manufacturers, the future of the industry will be placed in jeopardy, especially with reduced protection and incentives.
Keywords: Automobile industry and trade -- South Africa -- Eastern Cape; South Africa -- Commercial policy